2010
DOI: 10.1097/qai.0b013e3181cdebb1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Tolerability of Etravirine With and Without Darunavir/Ritonavir or Raltegravir in Treatment-Experienced Patients: Analysis of the Etravirine Early Access Program in the United States

Abstract: Etravirine combined with a BR, often including other new antiretrovirals, such as darunavir/ritonavir and/or raltegravir, provided an effective treatment option in treatment-experienced patients with HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
3
16
0
Order By: Relevance
“…ETR with raltegravir and darunavir (or other boosted PIs) has shown outstanding efficacy rates and a good safety profile in preliminary clinical trials and different expanded-access programs, achieving undetectable viral loads at 48 weeks in as many as 70% and 81% of patients after 48 weeks of treatment. 9,10,12,16 Our results are consistent with these findings, and darunavir and raltegravir were the most frequently used antiretroviral agents in the optimized baseline treatments, with high rates of treatment response and virological suppression. In addition, viral suppression has also been observed in 92% of patients in a setting with more limited therapeutic options, namely, a PI and NRTI-sparing regimen containing ETR plus maraviroc and raltegravir.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…ETR with raltegravir and darunavir (or other boosted PIs) has shown outstanding efficacy rates and a good safety profile in preliminary clinical trials and different expanded-access programs, achieving undetectable viral loads at 48 weeks in as many as 70% and 81% of patients after 48 weeks of treatment. 9,10,12,16 Our results are consistent with these findings, and darunavir and raltegravir were the most frequently used antiretroviral agents in the optimized baseline treatments, with high rates of treatment response and virological suppression. In addition, viral suppression has also been observed in 92% of patients in a setting with more limited therapeutic options, namely, a PI and NRTI-sparing regimen containing ETR plus maraviroc and raltegravir.…”
Section: Discussionsupporting
confidence: 94%
“…2,3 The safety and efficacy of ETR in combination with the remaining new antiretrovirals have not been evaluated outside the strictly controlled conditions of a clinical trial, although preliminary reports on the combination of these new drugs have shown promising results. [9][10][11][12] We evaluated the effectiveness of rescue regimens containing ETR combined with all the available active agents in routine clinical practice. We also analyzed the relationship between the 1 Lluita contra la SIDA, Hospital Universitari Germans Trias i Pujol, Badalona, Barcelona number of additional active drugs in the optimized regimen and other factors associated with the response to ETR.…”
Section: Introductionmentioning
confidence: 99%
“…This response was observed when etravirine was administered alone or when combined with raltegravir or darunavir-ritonavir. 57 The collection, analysis, and interpretation of the data by employees or individuals who had conflicts of interest with its manufacturer are among the limitations of the etravirine clinical trials. The pooled 24-week, individual 48-week, and pooled 48-week results of DUET-1 and DUET-2 have not been formally published.…”
Section: -Week Analysismentioning
confidence: 99%
“…71,72 Clinicians anticipate the final results of the Phase III early-access program trial and future etravirine trials to guide their selection of medications in the background regimen of etravirine. 45,57 Obtaining data on etravirine use with other antiretrovirals is especially important, because darunavirritonavir has been approved for treatment-naive patients, and the number of darunavir-ritonavir mutations in treatment-experienced patients may gradually increase.…”
Section: Role In Therapymentioning
confidence: 99%
“…Several clinical trials have reported a dramatic increase in the proportion of patients safely achieving virological response despite harboring multidrug-resistant HIV-1 viruses [8][9][10]. Among these investigations, the ANRS 139 TRIO trial reported that 86% of patients reached HIV-1 RNA < 50 copies/mL at week 48 with a salvage regimen containing raltegravir (RAL), ETV and DRV/r, and OBR with NRTIs or enfuvirtide [9].…”
Section: Introductionmentioning
confidence: 99%